Popular culture texts in education: The effect of tales transformed into children's media on critical thinking and media literacy skills - Ulu-Aslan, Emine; Bas, Bayram (ELSEVIER SCI LTD, 2023)
This study focuses on the effect of using postmodern tale films, which are based on the trans-formation of a text and enable multiple reading, as an educational tool on critical thinking and media literacy skills. In the study, which was structured as an embedded mixed design in order to achieve this aim, qualitative data were embedded in the experimental intervention and it was aimed that one data type play a supporting role for the other. The study group consists of 43 students studying at the 7th grade in an official secondary school in the province of Mus, in the fall semester of the 2021-2022 academic year. During the 8-week application period, while ac-tivities designed with media contents including the transformation of tales were practiced in the experimental group (n = 21), activities in the current Turkish textbook were practiced in the control group (n = 22). In this period, critical thinking skills test developed by Egmir and Ocak (2016), media literacy scale sensitive to entertainment purpose developed by the authors, semi-structured interview forms, and semi-structured observation form were used as data collection tools. It was concluded that the application designed with activities in which media contents containing tale transformations were used made a significant difference in favor of the experimental group on critical thinking and media literacy skills of students. In addition to this, observations made during these activities and products created by students showed that reflective and creative thinking skills were also positively affected in relation to critical thinking and media literacy skills. Quantitative data showing the results of these effects are supported by qualitative data helping to understand in which direction and how these effects occur.
Keywords: Children?s media; Intertextuality; Tale; Critical thinking; Media literacy; Education & Educational Research